Orthokeratology on patient with ectasic cornea - Dantas,Brunno (2019)
Abstract A 26-year-old man, single, business student, reveals a ectasic cornea during corneal topography exam. Among some procedures, the patient chose Orthokeratology to do a corneal reshape and got successfully a good visual acuity, going against the most authors guidance.